Mathematical Creative Thinking Process Analysis Based On Student Learning Style - Hamid, Amrin; Hamzah Upu; Jafaruddin, Jafaruddin (Cita konsultindo, 2025)
The creative thinking process of students needs to be developed to generate new ideas when solving mathematical problems. One of the causes of students' difficulties in developing a creative thinking process is different learning styles because differences can affect the student's understanding. This study aims to describe the creative thinking process of students in solving mathematical problems based on learning styles. The subjects of this study are 3 students of MTsN 1 Makassar, each representing one subject: visual, auditory, and kinesthetic learning styles. The study results showed that at the preparation stage, subjects with visual, auditory, and kinesthetic learning styles could carry out the creative thinking process well, as shown by expressing essential ideas from the questions. At the incubation stage, subjects with visual, auditory, and kinesthetic learning styles can develop ideas for solving problems by writing step by step. In the illumination stage, the subject's visual, auditory, and kinesthetic learning styles allow them to express their ideas verbally well. At the verification stage, the visual learning style has not been verified compared to other alternative solutions; auditory and kinesthetic always re-check the answers, re-verify the work results, and compare with other alternative solutions. Thus, auditory and kinesthetic subjects can produce creative thinking processes in solving mathematical problems based on indicators developed by Wallas. In contrast, visual subjects cannot produce creative thinking processes in solving mathematical problems based on indicators developed by Wallas.